Assessing the potential of VRS-RTK in structural health monitoring - Nordin, Zuhaidah (Faculty of Geoinformation Science And Engineering, 2009)
Rapid growth in construction of large engineering structures such as dams, wide span bridges, highways, breakwater and high rise buildings are mainly essential for the development of a nation. Aging from these national structural inventories and the fact that many large engineering structures are carrying greater average loads than predicted during their designing stage, have significantly increased the need to monitor their health and stability performance. In order to ensure the safety and serviceability of these structures as well as to prevent disastrous consequences due to structural displacement, periodic monitoring and in-depth analysis of their structural behaviour based on a large set of variables contributing to the deformation are highly demanded. With advanced development of space-base positioning technique, GPS is one of the latest all-weather satellite-based sensors that can be used to detect first stage disaster and further mitigation. This study highlights the use of GPS network-based VRS-RTK technique for real-time structural health monitoring. Several tests have been conducted, including indoor observation at Topcon Building in Kuala Lumpur, breakwater monitoring in Kemaman, Terengganu and monitoring of the P23 Building, Faculty of Mechanical Engineering, Universiti Teknologi Malaysia. The study has proved that VRS-RTK have potential to be as accurate yet practical positioning tools used for Structural Health Monitoring. Provided that proper instrumentation setup applied during data acquisition, VRS-RTK is as well suitable in various monitoring environment either at outdoor or indoor area. On the basis of the structural health, no significant deformation detection have been observed for all these campaigns.